Perspectives of Nursing Homes Staff on the Nature of Residents-Initiated Call Lights - Haneen Ali PhD; Astin Cole MPA; Adam Sienkiewicz BA; Tori Ho BA (SAGE Publishing, 2020)
Little research has been conducted to capture the perceptions of nursing home staff when using the call light system. There is also a lack of information regarding the effects that these perceptions of the call light system have on their workload, safety, quality of care, or overall satisfaction. In response to the high volume of complaints from residents and their families regarding long response times to call light alarms, we developed this exploratory cross-sectional survey study. This study aims to capture nursing home staff experiences while using a call light system; to investigate the challenges the staff face when using the system; and to determine how these challenges contribute to their workload, performance, and satisfaction. A survey instrument was developed and distributed to all 153 of the nursing staff, certified nursing assistants, and licensed practical nurses in a nursing home in upstate New York. A total of 105 completed surveys were retrieved for an overall response rate of 68.63%. Descriptive analysis, Pearson correlation, and the Kruskal-Wallis test were used to analyze the collected data. The results showed a significant correlation between the processes of being notified and locating call light alarms and workload. The staff reported many usability challenges that may contribute to longer response time such as lack of prioritization, low/no discriminability, noise, and overwrite previous alarm. In addition, 78% of the staff agreed that responding to a call light can prevent serious harm; however, 56% of the staff agreed that call light system is not meaningful; and around 78% think that call light system is disruptive in the environment and source for constant noise. The study finds that incorporating the insights provided by nursing home staff may improve the acceptance of new and existing technology, which ultimately improves the delivery of care through greater usability.